Aksi Bersih Dan Penanaman Bibit Mangrove Di Desa Poka Kecamatan Teluk Ambon - Rahman, Rahman; Pasanea, Krisye; Haumahu, Sara; Supusepa, Junita (Pakis Journal Institute, 2024)
The environments that receive the greatest impact from waste generation are coastal and marine areas. This is because waste dumped in gutters and rivers will flow to coastal areas and the sea. One of the ecosystems that receives the impact of waste disposal is mangroves. Poka Village is a coastal area in Inner Ambon Bay with a fairly dense population. One of the vegetation that is an important concern for people living in this area is mangroves. This is because there was sudden damage to mangroves in May 2022 due to oil waste. Quick and appropriate action needs to be taken immediately to preserve the mangrove ecosystem in Poka Village. Therefore, it is necessary to carry out clean-up actions and plant mangrove seedlings in Poka Village in the damaged mangrove ecosystem. The service activity took place in Poka Village on May 11 2023. The service was carried out together with the NGO Moluccas Coastal Care, the State Electricity Company (PLN), the Army, students and lecturers of Marine Science at Pattimura University and also the community in Poka Village. The activity began with a gathering at the mangrove planting location at 08:00 WIT. After that, clean up the rubbish and cut down the dead mangrove trees. Then proceed with planting Rhizhopora sp mangrove seedlings. Planted mangrove seeds can grow well after one year. This indicates that environmental conditions such as substrate and water are in good condition and suitable for the growth of mangrove seedlings. Future monitoring activities need to be carried out to maintain the successful growth of mangrove seedlings from year to year.